Examining the Implementation Fidelity and Stakeholder Value in the Malawi Government Graduate Internship Programme (African Journal of Public Administration & Management, 2026)
Fresh graduates are usually unable to transition smoothly intoemployment due to employers’ high expectations for abilities andpersonal qualities (Helyer and Lee, 2014). Sub-Saharan Africa needs 25 million new jobs annually (World Bank,2025). Malawi’s youth unemployment rate is at 23%. The Ministry of Labour in Malawi has been implementing theGraduate Internship Programme (GIP) since 2018, reaching 20232graduates (11 cohorts) with the to provide work-integrated experienceto improve their employability